PEMBELAJARAN MENULIS TEKS PIDATO DENGAN MODEL THINK TALK WRITE DI KELAS IX SMP NEGERI 6 KOTA SERANG - Meti Istimurti (Universitas Sultan Ageng Tirtayasa, 2016)
Writing activities are an integral part of the whole process of learning Indonesian language and literature. Facing the teaching of writing, especially writing text to speech many students are looking at a difficult activity. The work was undertaken in SMP Negeri 6 Serang. The research was conducted in January – the beginning of March 2015. The subjects were students of class IX B totaling 38 people, as the recipient of the action, with the consideration of this class is a class whose average value is lower than the write another class. The perpetrator is a teacher Indonesian IX class, and assisted by other teachers as observers. The data used in this research is the process of learning to write text to speech talk think write the model and student learning outcomes in the form of a product according to the text of a speech that indicators of success. This study uses classroom action research (Classroom Action Research). Collecting data in this study was conducted through literature review, observation, field notes, drawings and performance assessment. The data analysis is done collaboratively, since the study began, during the action takes place, and developed during the process of reflection to the preparation of the report. Data analysis technique used is an interactive model according to Huberman, namely data reduction, data presentation, and conclusion. In this study, the conclusions obtained the ability to write text to speech class IX students of SMP Negeri 6 Serang said is still lacking, this is evidenced by the results of tests of creative writing with an average value of 58.40. The use of models of instructional talk think write may actually enhance the ability to write text to speech class IX students of SMP Negeri 6 Serang city, this is evidenced by the achievement of the average value has increased. In the first cycle the average value reached 64.86 and the second cycle the average yield reached 74.56 value. Likewise the achievement of mastery learning creative writing, has increased significantly from 20.05% in prasiklus, 43.10 and 86.64 in the first cycle in the second cycle.